IMPLEMENTASI PENEGAKAN DISIPLIN DALAM PROSES PEMBELAJARAN SOSIOLOGI DI KELAS XI IPS 2 SMAK ABDIWACANA PONTIANAK - Rudianto Rudianto; Izhar Salim; Imran Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed to find out the general problems in this study, namely How Implementation of Discipline Enforcement in the Sociology Learning Process in Class XI IPS 2 of SMAK Abdiwacana Pontianak, with sub-problems: 1) How is the Implementation of Enforcement of Time Discipline? 2) How is the Implementation of Enforcement Discipline Enforcing Rules? 3) How is the Implementation of Attitude Discipline Implemented? 4) How is the Implementation of Discipline Enforcement of Worshiping? The form of research used in this study is qualitative research with descriptive research methods. The results of this study are the implementation of time discipline enforcement carried out by teachers based on special rules following sociology learning. Implementation of enforcement of discipline enforces rules is carried out by the teacher if the student concerned is proven to violate the rules agreed upon beforehand, students will be given notice, reprimand, warning and even punishment. Implementation of attitude discipline enforcement is carried out by the teacher if students do not comply with the applicable rules. The rules are made so that students are accustomed to discipline and forming strong and resilient student behaviors. The implementation of disciplinary enforcement in carrying out worship is carried out by the teacher by telling students to lead praying together before the learning process begins. Keywords: Enforcement Of Discipline, The Study Of Sociology, SMAK.